Malaysian Government-Linked Companies and Earnings Management: The Interaction Effects of Internal And External Governance Mechanisms - Ma, Wyei Leng; Sulaiman, Noor Adwa; Abdul Jalil, Azlina (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
This study aims to explore the interaction effects of the audit committee (AC), the internal audit function (IAF), as well as the external auditors (EA) toward earnings management between government-linked companies (GLCs) in Malaysia. This study used regression analysis on 340 firm-year-based observations with Malaysian GLCs available on the Bursa Malaysia main board during the 2009 – 2018. This study found that the interaction between the AC and the IAF is significantly and negatively correlated with EM. However, the AC's interaction with the EA shows an insignificant relationship in reducing EM. Additionally, the interaction between EA and the IAF negatively affects EM. It is one of the first papers to explore the complementary impact of external and internal corporate governance functionality or mechanisms on EM.